Notch Effect on Plastic Deformation of Metallic Glass: A Numerical Study by Revised Free-Volume Theory - J. F. Yan; W. J. Meng; Z. Chen; H. Guo; X. G. Yan (Advances in Materials Science and Engineering)
By means of a revised free-volume theory, the notch effect on metallic glass was systematically investigated by the numerical method. Simulations on specimens without notches demonstrated that the parameters being determined in this work could reasonably describe the strength asymmetry of tension and compression. Moreover, four samples with different notches were used to numerically investigate the notch effect on global strength and plasticity. A better agreement could also be achieved between current simulations with existing experimental results, compared with another free-volume model. Combined with the free-volume distribution during deformation process, it was proven that the intersection of two major shear bands is the cause for the strength and plasticity enhancement found in sample with two symmetric notches. Besides, strength asymmetry between tension and compression was also found for notched samples. Compressive strengths are accordingly higher than tensile ones. Moreover, with the augment of the aspect ratio, the plasticity for specimens with two symmetric notches was found to increase firstly and then decrease afterwards.